The Importance of Using Action Games in the Training of Young Football Players (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article describes the development of dexterity, grasping, aiming, logical and quick-thinking qualities of young football players with the help of mobile games and game exercises, and the views of experts on this topic are highlighted.